THE WEIGHT OF THE BURSA OF FABRICIOUS IN SELECTED CHICKENS DEPENDING ON RESISTANCE OR SENSITIVITY TO STRESS - H. Z. , AL-SAM (The Iraqi Journal of Veterinary Medicine, 1996)
Mean body weight and body temperature of chickens selected from known parents of groups (sensitive and resistant to stress) were measured weekly. No significant difference was found. Weight of the bursa of Fabricious was significant at week 15.